Randomized multicenter study of multiple plastic stents vs. covered self-expandable metallic stent in the treatment of biliary stricture in chronic pancreatitis - Haapamäki, Carola; Kylänpää, Leena; Udd, Marianne; Lindström, Outi; Grönroos, Juha; Saarela, Arto; Mustonen, Harri; Halttunen, Jorma (Endoscopy, 2015)
Background and study aims: The use of covered self-expandable metallic stents (cSEMS) in benign biliary indications is evolving. The aim of the study was to assess the safety and feasibility of cSEMS compared with multiple plastic stents in the treatment of benign biliary stricture (BBS) caused by chronic pancreatitis.Patients and methods: This was a prospective, multicenter, randomized study of 60 patients with BBS caused by chronic pancreatitis. All patients received an initial plastic stent before randomization. At randomization, the stent was replaced either with a single cSEMS or three plastic stents. After 3 months, the position of the cSEMS was checked or another three plastic stents were added. At 6 months after randomization, all stents were removed. Clinical follow-up including abdominal ultrasound and laboratory tests were performed at 6 months and 2 years after stent removal. Results: Two patients dropped out of the cSEMS group before stent removal. In April 2014, the median follow-up was 40 months (range 1 – 66 months). The 2-year, stricture-free success rate was 90 % (95 % confidence interval [CI] 72 % – 97 %) in the plastic stent group and 92 % (95 %CI 70 % – 98 %) in the cSEMS group (P = 0.405). There was one late recurrence in the plastic stent group 50 months after stent removal. Stent migration occurred three times (10 %) in the plastic stent group and twice in the cSEMS group (7 %; P = 1.000).Conclusion: A 6-month treatment with either six 10-Fr plastic stents or with one 10-mm cSEMS produced good long-term relief of biliary stricture caused by chronic pancreatitis.Study registered at ClinicalTrials.gov (NCT01085747).